2022
DOI: 10.4209/aaqr.210258
|View full text |Cite
|
Sign up to set email alerts
|

Filtration of Submicron Soot Particles, Oil Droplets, and their Mixtures on Single- and Multi-layer Fibrous Filters

Abstract: The dynamics of filtration efficiency and pressure drop during the simultaneous filtration of soot and oil aerosols on single-and multi-layer filters were investigated, and the determined filtration efficiency was compared with the theoretical efficiency obtained via the classical filtration theory. Additionally, the influence of liquid-phase aerosols on the morphology of the formed deposits was investigated. It was concluded that the addition of oil aerosols decreased the filtration efficiency and lowered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A simultaneous filtration of solid and liquid particles was investigated in our last work. By examining the simultaneous filtration of soot particles and water droplets [ 35 ], as well as soot particles and oil droplets [ 36 ], we observed similar effects as in the case of alternate filtration: the collapse of the filter deposits leading to a decrease in efficiency and the evolution of the pressure drop similar to the filtration of liquid aerosols.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A simultaneous filtration of solid and liquid particles was investigated in our last work. By examining the simultaneous filtration of soot particles and water droplets [ 35 ], as well as soot particles and oil droplets [ 36 ], we observed similar effects as in the case of alternate filtration: the collapse of the filter deposits leading to a decrease in efficiency and the evolution of the pressure drop similar to the filtration of liquid aerosols.…”
Section: Introductionmentioning
confidence: 83%
“…The electrostatic mechanism was omitted due to the filtration material not being charged with static charges (samples were neither intentionally charged nor discharged; however, the existence of some charges related to the manufacturing process may still be possible). The filtration efficiency calculations and its changes over time were based on the following empirical equations which were discussed in detail in our previous papers [ 36 , 42 ]: where η dif —diffusion mechanism efficiency (-), Pe—Peclet number (-), η int —interception mechanism efficiency (-), α—packing density (-), Ku—hydrodynamic factor of Kuwabara flow (-), R—interception parameter (-), η imp —impaction mechanism efficiency (-), and Stk—Stokes number (-).…”
Section: Methodsmentioning
confidence: 99%
“…Studies utilizing microscopy for characterizing challenged filter surfaces are scarce. Observation of "beading" morphologies was observed in several publications focusing on liquid-phase organic aerosols [82,85].…”
Section: Effect Of Smoke Loading On the Filtration Efficiency And Mor...mentioning
confidence: 95%
“…The dynamics of the liquid and solid particle filtration differ significantly due to the differences in deposition modes (dendritic structures formed by solid particles vs. film formation by liquids), collision kinetics, and differences in the particle/fiber surface interactions. Some studies indicated that the presence of oil in the particle causes a reduction in the media's filtration efficiency in comparison to solid particles of the same size [82]. Numerous studies have shown that the MPPS for non-charged (mechanical) filter media lies indeed in the 0.1 to 0.3 µm range, while for electret media, it is around 20-30 nm [53,79].…”
Section: Characterization Of Initial Filtration Efficiency Of Pine Ne...mentioning
confidence: 99%
“…Air purification filter materials made of charged melt-blown polypropylene microfibers are the key consumable to determine the level of air purification system [ 8 ]. Filtration efficiency and dust holding performance are two key standards to evaluate the filter materials, which are mainly affected by fiber dimension filling degree, filter material structure and some environmental factors [ 9 , 10 ]. When the filter materials are processed into air-cleaner element, pleats or folds are usually used to provide a larger filtration area than traditional flat filters by decreasing the amount of space between each layer of material and also allow more particles to be trapped in the filter, resulting in greater effectiveness and efficiency [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%